Active Learning in Arabic Syntax (Nahwu): An Innovative Strategy for Islamic University Students in the 21st Century - Setiadi, Agung Heru; Mahdi, Tubagus Ahmad; Asy’arie, Bima Fandi; Hijriyah, Umi; Aziz, Mahbub Humaidi (Borneo Journal of Language and Education, 2025)
This study aims to determine the orientation and steps of Nahwu learning in Arabic I courses. Then analyze the obstacles in Nahwu learning and the factors that cause these obstacles. This research was conducted at the Faculty of Sharia, UIN Sultan Maulana Hasanuddin Banten, using a qualitative research design with a case study type. The results of this study indicate that. Nahwu learning at the Faculty of Sharia is oriented towards active learning with inductive learning strategies and individual conventional learning techniques. The learning steps refer to the components of educational and teaching methods and are based on PAIKEM. The problem of learning Nahwu consists of (a) supporting factors, including internal factors, including the physical condition of students, student competence, student tendencies, and motivation; external factors, including the Arabic language environment, the presence of native speakers, competent lecturers, teaching materials, exercises, and reward and punishment systems. (b) Inhibiting factors include internal factors, including student self-confidence and differences in student backgrounds, as well as lack of student motivation and commitment, lack of Arabic language environment, and low effectiveness of efforts; external factors include lack of supervision and recording, changes in course schedules, and lack of learning media.